Seed coat colour of Indian mustard [Brassica juncea (L.) Czern. and Coss.] is associated with Bju.TT8 homologs identifiable by targeted functional markers - Patel, Manoj Kumar; Chaudhary, Rajat; Taak, Yashpal; Pardeshi, Priya; Nanjundan, Joghee; Vinod, K. K.; Saini, Navinder; Vasudev, Sujata; Yadava, D. K. (Frontiers in Plant Science, 2022)
Seed coat colour is an important trait in Indian mustard. Breeding for seed coat colour needs precise knowledge of mode of inheritance and markers linked to it. The present study was focussed on genetics and development of functional markers for seed coat colour. F1s (direct and reciprocal) and F2 populations were developed by crossing two contrasting parents for seed coat colour (DRMRIJ-31, brown seeded and RLC-3, yellow seeded). Phenotypic results have shown that the seed coat colour trait was under the influence of maternal effect and controlled by digenic-duplicate gene action. Further, Bju.TT8 homologs of both parents (DRMRIJ-31 and RLC-3) were cloned and sequenced. Sequencing results of Bju.TT8 homologs revealed that in RLC-3, gene Bju.ATT8 had an insertion of 1279bp in the 7th exon; whereas, gene Bju.BTT8 had an SNP (C→T) in the 7th exon. These two mutations were found to be associated with yellow seed coat colour. Using sequence information, functional markers were developed for both Bju.TT8 homologs, validated on F2 population and were found highly reliable with no recombination between the markers and the phenotype. Further, these markers were subjected to a germplasm assembly of Indian mustard, and their allelic combination for the seed coat colour genes has been elucidated. The comparative genomics of TT8 genes revealed high degree of similarity between and across the Brassica species, and the respective diploid progenitors in tetraploid Brassica species are the possible donors of TT8 homologs. This study will help in the marker-assisted breeding for seed coat colour, and aid in understanding seed coat colour genetics more precisely.